Historical biogeography of the Isthmus of Panama. (19th July 2013) - Leigh, Egbert G.; O'Dea, Aaron; Vermeij, Geerat J.
ABSTRACT About 3 million years ago (Ma), the Isthmus of Panama joined the Americas, forming a land bridge over which inhabitants of each America invaded the other—the Great American Biotic Interchange. These invasions transformed land ecosystems in South and Middle America. Humans invading from Asia over 12000 years ago killed most mammals over 44 kg, again transforming tropical American ecosystems. As a sea barrier, the isthmus induced divergent environmental change off its two coasts—creating contrasting ecosystems through differential extinction and diversification. Approximately 65 Ma invading marsupials and ungulates of North American ancestry, and xenarthrans of uncertain provenance replaced nearly all South America's non‐volant mammals. There is no geological evidence for a land bridge at that time. Together with rodents and primates crossing from Africa 42 to 30 Ma, South America's mammals evolved in isolation until the interchange's first heralds less than 10 Ma. Its carnivores were ineffective marsupials. Meanwhile, North America was invaded by more competitive Eurasian mammals. The Americas had comparable expanses of tropical forest 55 Ma; later, climate change confined North American tropical forest to a far smaller area. When the isthmus formed, North American carnivores replaced their marsupial counterparts. Although invaders crossed in both directions, North American mammals spread widely, diversified greatly, and steadily replaced South American open‐country counterparts, unused to effective predators. Invading South American mammals were less successful. South America's birds, bats, and smaller rainforest mammals, equally isolated, mostly survived invasion. Its vegetation, enriched by many overseas invaders, remained intact. This vegetation resists herbivory effectively. When climate permitted, South America's rainforest, with its bats, birds and mammals, spread to Mexico. Present‐day tropical American vegetation is largely zoned by trade‐offs between exploiting well‐watered settings versus surviving droughts, exploiting fertile versus coping with poor soil, and exploiting lowland warmth versus coping with cooler altitudes. At the start of the Miocene, a common marine biota extended from Trinidad to Ecuador and western Mexico, which evolved in isolation from the Indo‐Pacific until the Pleistocene. The seaway between the Americas began shoaling over 12 Ma. About 10 Ma the land bridge was briefly near‐complete, allowing some interchange of land mammals between the continents. By 7 Ma, the rising sill had split deeper‐water populations. Sea temperature, salinity and sedimentary carbon content had begun to increase in the Southern Caribbean, but not the Pacific. By 4 Ma, the seaway's narrowing began to extinguish Caribbean upwellings. By 2 Ma, upwellings remained only along Venezuela; Caribbean plankton, suspension‐feeding molluscs and their predators had declined sharply, largely replaced by bottom‐dwelling corals and calcareous algae and magnificent coral reefs. Closing the seaway extinguished the Eastern Pacific's reef corals (successors recolonized from the Indo‐Pacific 6000 years ago), whereas many molluscs of productive waters that once thrived in the Caribbean now survive only in the Eastern Pacific. The present‐day productive Eastern Pacific, with few, small coral reefs and a plankton‐based ecosystem contrasts with the Caribbean, whose clear water favours expansive coral reefs and bottom‐dwelling primary producers. These ecosystems reflect the trade‐off between fast growth and effective defence with attendant longevity. Overfishing with new technologies during the last few centuries, however, has caused population crashes of ever‐smaller marine animals, devastating Caribbean ecosystems.